2014
DOI: 10.1016/j.pharep.2014.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Silymarin liposomes improves oral bioavailability of silybin besides targeting hepatocytes, and immune cells

Abstract: Incorporating the phytosomal form of silymarin in liposomal carrier system increased the oral bioavailability and showed better hepatoprotection and better anti-inflammatory effects compared with silymarin suspension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(33 citation statements)
references
References 20 publications
0
33
0
Order By: Relevance
“…Silymarin may enhance three available growth factors (HGF, TGF α , and TGF β 1), acting as a cell cycle progression agent that triggers liver regeneration to protect the liver as a hepatoprotective agent for liver disease. HGF is a mitogenic agent for many different cell types with major effects on liver hepatic growth [ 11 13 ]. Matrix breakdown may cause a rapid release of HGF into the plasma, which occurs shortly after PHx [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Silymarin may enhance three available growth factors (HGF, TGF α , and TGF β 1), acting as a cell cycle progression agent that triggers liver regeneration to protect the liver as a hepatoprotective agent for liver disease. HGF is a mitogenic agent for many different cell types with major effects on liver hepatic growth [ 11 13 ]. Matrix breakdown may cause a rapid release of HGF into the plasma, which occurs shortly after PHx [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The increase in the bioavailability of silymarin using a nanoemulsion might be due to the higher solubilization of drug in oil. Moreover, the presence of a surfactant and cosurfactant in the nanoemulsion system might have caused changes in the membrane permeability, and was able to reach a maximum concentration in minimum possible time [39,40]. Consequently, the present study showed rapid onset and better absorption of orally administered silymarin nanoemulsion than before.…”
Section: Accelerated Stability Studiesmentioning
confidence: 55%
“…It has been widely researched experimentally and clinically and its application has been widely used in many fields, especially in medical engineering. As a drug carrier, liposome has the characteristics of improving drug efficacy, reducing adverse drug reactions and targeting 32 .…”
Section: ■ Discussionmentioning
confidence: 99%